Efficacy and safety of novel oral anticoagulants for treatment of acute venous thromboembolism: direct and adjusted indirect meta-analysis of randomised controlled trials. (13th November 2012) - Fox, Benjamin D; Kahn, Susan R; Langleben, David; Eisenberg, Mark J; Shimony, Avi
Abstract : Objective To critically review the effectiveness of the novel oral anticoagulants (rivaroxaban, dabigatran, ximelagatran, and apixaban) in the treatment of acute venous thromboembolism. Design Systematic review and random effects meta-analysis. Data were extracted independently by two investigators. An adjusted indirect comparison was performed to compare between novel oral anticoagulants. Data sources Medline, Embase, and Cochrane Library (from inception to April 2012). Hand searching of relevant scientific works and contact with experts. Study selection Randomised controlled trials of novel oral anticoagulants compared with vitamin K antagonists for acute venous thromboembolism. Selected outcomes were recurrent events, major bleeding, and all cause mortality. Results Nine studies met our inclusion criteria, involving 16 701 patients evaluated for efficacy and 16 611 for safety. Data were stratified according to different novel oral anticoagulants. For recurrent acute venous thromboembolism, there were no significant differences in events rates between any of the anticoagulants and conventional treatment (rivaroxaban (four studies): relative risk 0.85, 95% confidence interval 0.55 to 1.31; dabigatran (two studies): 1.09, 0.76 to 1.57; ximelagatran (two studies): 1.06, 0.62 to 1.80; and apixaban (one study): 0.98, 0.20 to 4.79). Rivaroxaban reduced the risk of major bleeding compared with conventional treatment (0.57, 0.39 to 0.84), whereas other novel oral anticoagulants did not (0.76 (0.49 to 1.18) for dabigatran; 0.54 (0.28 to 1.03) for ximelagatran; 2.95 (0.12 to 71.82) for apixaban). For all cause mortality there were no significant differences between the novel oral anticoagulants and conventional treatment (0.96 (0.72 to 1.27) for rivaroxaban; 1.00 (0.67 to 1.50) for dabigatran; 0.67 (0.42 to 1.08) for ximelagatran; 6.89 (0.36 to 132.06) for apixaban). The adjusted indirect comparison between rivaroxaban and dabigatran did not show superiority of either drug over the others for major bleeding (0.75, 0.41 to 1.34) or the other endpoints. Conclusions Compared with vitamin K antagonists, the novel oral anticoagulants had a similar risk of recurrence of acute venous thromboembolism and all cause mortality, though rivaroxaban was associated with a reduced risk of bleeding.